University organisational culture : conceptualisation, construction, and test of relationships with organisational change initiatives and attitude toward change - Mohd Ferdaus Harun (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2020)
Most of organisational change projects neither result in their intended aims nor foster sustained change. This trend is more alarming for higher education institutions (HEI) since they are constantly undergoing organisational change. Research on organisational change and development have highlighted human factors such as organisational culture and attitudes toward change as the missing link to explain this failure. However, limited studies have attempted to analyse the effects of organisational culture during the implementation of change initiatives, especially in HEI due to the conceptualisation and operationalisation issues. The available conceptualisation of organisational culture has been found to be multiple, atheoretical, and anecdotal. Furthermore, quantitative analysis of this construct has been surrounded by psychometric issues. Therefore, the present study aspires to address these issues and aims to conceptualise University Organisational Culture, to construct a new measure of University Organisational Culture, and to investigate the effects of University Organisational Culture on the implementation of organisational change initiatives and five attitudes toward change (i.e., readiness for change, openness toward change, commitment to change, cynicism about organisational change, & resistance to change). These objectives were operationalised through two sub-studies. Firstly, test development procedures were employed to systematically conceptualise University Organisational Culture from three main processes; review of research, interviews with subject-matter experts, and content analysis. A new multi-level (cognitive, affective, & behavioural levels) and multi-dimensional (Mission, Leadership, Strategy, Information, Environment, Socialisation, & Operation) conceptualisation of University Organisational Culture was proposed and used to develop a Situational Judgement Test of University Organisational Culture. Evaluation of content validity by 12 test development experts indicate 107 out of 191 items demonstrate high content validity. Secondly, this new measure was then used to investigate the relationships between the implementation of organisational change initiatives and the five attitudes toward change. A cross-sectional survey using a questionnaire was employed. Monte-Carlo simulation was conducted to estimate sample size, which resulted in a total of 426 respondents recruited using systematic random sampling procedures from a Malaysian university. Results of the measurement model of PLS-SEM indicate that the seven dimensions of University Organisational Culture were relevant and significant to measure the construct. Furthermore, results of the structural model found that the implementation of organisational change initiatives has a positive effect on employees' readiness for change and have negative effects on the commitment, cynicism, and resistance to change. In addition, University's Organisational Culture was found to have positive effects on readiness for change as well as openness towards change, and negative effects on commitment, cynicism, and resistance to change. Furthermore, the University Organisational Culture was found to significantly moderate the relationships between the implementation of organisational change initiatives and employees' commitment, cynicism, and resistance to change. Significance of these findings was discussed in light of the findings of previous research. These findings contribute to the theoretical understanding, quantitative analysis, and practical application in the organisational change of HEI.